2016
DOI: 10.5897/ajmr2016.8056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biofilms on urinary catheters using immobilized Lactobacillus cells

Abstract: Bacterial biofilms forming on indwelling urinary catheters continue to represent a public health problem because they are associated with urinary tract infections (UTIs). This study was undertaken to evaluate the ability of immobilized Lactobacillus acidophilus cells to inhibit biofilm formation on catheter surfaces. Urine bacteria and Lactobacillus species were isolated from urine and vaginal swabs (HVS), respectively. Immobilization of L. acidophilus on catheter samples was achieved using sodium alginate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, 6 days were not enough to clear P. aeruginosa by any of the tested probiotic strains. The results of this study strongly agree with those of Ifeoma and Jennifer, in which pre-coating of catheter surfaces with L. acidophilus before exposure to bacterial uropathogens significantly reduced the attachment of E. coli and Klebsiella to the catheter surfaces, while P. aeruginosa was not inhibited [29]. The results of the current study also agree with those of Maldonado et al, in which whole cells and acid supernatant of L. fermentum inhibited BF and growth of Klebsiella [30].…”
Section: Groupsupporting
confidence: 92%
“…However, 6 days were not enough to clear P. aeruginosa by any of the tested probiotic strains. The results of this study strongly agree with those of Ifeoma and Jennifer, in which pre-coating of catheter surfaces with L. acidophilus before exposure to bacterial uropathogens significantly reduced the attachment of E. coli and Klebsiella to the catheter surfaces, while P. aeruginosa was not inhibited [29]. The results of the current study also agree with those of Maldonado et al, in which whole cells and acid supernatant of L. fermentum inhibited BF and growth of Klebsiella [30].…”
Section: Groupsupporting
confidence: 92%
“…Despite promising results in displacing adhering uropathogens and inhibiting bacterial adhesion to catheter materials [40][41][42][43][44][45][46][47][48], the application of probiotics as a coating for UTDs remains barely explored. Since bacterial adhesion and biofilm growth are affected by the hydrodynamic forces around surfaces [49], and these forces vary between the upper and lower urinary tract, as well as on the inner and outer part of the device, it is important to consider this variability when setting an experimental assay of biofilm formation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments should also use biologically relevant fluids like pooled human urine or artificial urine [9]. Most of the antibiofilm assays are performed under static conditions [40,[43][44][45][46], characteristic of the extraluminal side of UTDs [9], while just a small number of studies used the controlled hydrodynamic conditions [47,48] from intraluminal surfaces in the urethra, bladder or ureter [9]. On the other hand, only a couple of studies used nutritional conditions similar to those found in human urine [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics were successfully tested on silicone-based surfaces, decreasing the amount of biofilm culturable cells of S. aureus (99.9%), Ent. faecalis (99.9%) and multi-species biofilms (83%–95%) ( Table 1 , Table 2 and Table 3 ), showing applicability in urinary catheters [ 12 , 94 , 107 , 126 ] and voice prostheses [ 60 , 92 ]. Moreover, probiotics exerted antibiofilm activity on polystyrene ( Table 2 and Table 3 ), reducing the biofilm culturability of E. coli [ 93 , 105 ] and K. pneumoniae [ 110 ] up to 99.9%, and the biofilm amount of Strep.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic cells also reduced the number of biofilm culturable cells of C. albicans up to 80% in polyurethane ( Table 1 and Table 3 ) [ 87 ], and of E. coli O157:H7, S. aureus and S. epidermidis up to 99.9% in polypropylene ( Table 3 ) [ 113 ]. In glass, the introduction of L. rhamnosus and Lactobacillus reuteri into pre-formed biofilms resulted in a significant killing of pathogens ( Table 1 ) [ 89 , 93 ], while the L. acidophilus coating demonstrated high resistance to bacterial adhesion ( Table 2 ) [ 107 ]. Other applications where probiotics have been gaining interest are in the oral biofilm treatment and caries prevention.…”
Section: Resultsmentioning
confidence: 99%